Insight into the sunlight-driven photocatalytic activity of ZnO and ZnO/Ag hybrid nanostructures - Samriti; Astha Pujara; Sahil Thakur; Tapas Palai; Rajeev Gupta; H.C. Swart; Andrej Kuznetsov; Jai Prakash (Next Materials)
Developing efficient and sustainable photocatalysts for environmental remediation remains a critical challenge. This study presents a straightforward sol-gel synthesis method for ZnO nanoparticles (NPs) and ZnO/Ag hybrid NPs aiming to investigate sunlight-driven photocatalytic activity and long-term stability towards removal of dye pollutants in wastewater. The ZnO/Ag hybrid NPs containing embedded Ag nanocrystals (NCs) showed excellent visible light absorption due to surface plasmon resonance properties of Ag NCs. The photocatalytic activity was assessed using methylene blue (MB) dye under both UV and direct sunlight. Interestingly, pure ZnO NPs demonstrated superior photocatalytic efficiency achieving over 98 % degradation of MB within 45 min, likely due to their higher surface area and porosity as compared to that of ZnO/Ag plasmonic hybrid NPs. These results highlight that while Ag NCs embedding in ZnO NPs enhances the optical properties of ZnO, however, it does not necessarily improve the photocatalytic efficiency which has been studied in detail and a mechanism has been proposed. In addition, these photocatalyst were investigated for reproducibility and recyclability as well as for long term stability. Such plasmonic nanohybrids demonstrate great potential for versatile and long-term applications as highly recyclable SERS substrates as well as durable photocatalysts in environmental applications.